RELATIONSHIP BETWEEN HEALTH SERVICES AND PATIENT SATISFACTION FROM THE SOCIAL SECURITY AGENCY (BPJS): A LITERATURE REVIEW - Endarwati, Wa Ode Khofifah; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Hospital is an establishment engaged in the provision of healthcare services. The government must ensure that individuals have access to health services, which is considered a fundamental right. Hospital is one type of facility that is established and operated by the government. Despite this, a significant number of Indonesians continue to lack access to health services Priority must be given to ensuring patient satisfaction when implementing services. An element contributing to patient discontentment is the inadequate level of attention provided by hospitals, particularly to inpatients utilizing Badan Penyelenggara Jaminan Sosial (BPJS) services. The research approach employed was a narrative review of articles retrieved from databases such as PubMed and Google Scholar, utilizing the search terms "health services, BPJS patients." A total of nine research articles were chosen in alignment with the objectives of the literature review. This article comprised cross-sectional and descriptive research. An element that might impact patient contentment was the standard of nursing services. A range of complaints arose as a result of patient dissatisfaction resulting from substandard service. An increase in complaints served as an indicator of substandard service, potentially leading to a decline in patient satisfaction. As a result, it is imperative to propose enhancements to healthcare provisions in order to increase patient satisfaction Keywords: BPJS, health services, patients.